PENGARUH GREEN MARKETING, GREEN BRAND IMAGE, DAN GREEN KNOWLEDGE TERHADAP KEPUASAN PELANGGAN PRODUK CLEO ECO GREEN DI WILAYAH SURABAYA - Savitri, Sani; Marlena, Novi (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
The purpose of this study was to determine the effect of green marketing, green brand image, and green knowledge on customer satisfaction for Cleo Eco Green products in the Surabaya area. The population in this study were all customers who had purchased Cleo Eco Green products in Surabaya. The sample consisted of 124 respondents who had purchased Cleo Eco Green products with more than 3 purchases. The sampling technique used purposive sampling. The data collection technique uses an online questionnaire via the Google form. Data analysis used multiple linear regression analysis processed with SPSS 20. The results of this study prove that there is an influence of green marketing, green brand image, and green knowledge on customer satisfaction for Cleo Eco Green products in the Surabaya area.